2017
DOI: 10.1016/j.jwpe.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of barium-modified analcime in sulphate removal: Isotherms, kinetics and thermodynamics studies

Abstract: Analcime and commercial zeolite were employed as a precursor for preparing sorbent material for SO4 2removal over barium modification. Three sorbents were prepared: barium-modified analcime (ANA-Na-Ba), barium-modified acid-washed analcime (ANA-Ac-Na-Ba) and bariummodified zeolite (ZSM5-Na-Ba). Of the prepared materials, ANA-Ac-Na-Ba was the most efficient sorbent material for SO4 2removal, with a maximum sorption uptake of 13.7 mg g -1 at room temperature. Batch sorption experiments were performed to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…Under the specific conditions of this approach, a pH of 4 was determined optimal for sulfates adsorption. In the recent approach of Runtti et al (2017), adsorption of sulfates onto natural and/or modified zeolites has been shown to be effective under the lowest pH conditions (<6). These authors suggested that the enhancement of adsorbent state of protonation under acidic conditions favoured sulfates uptake.…”
Section: Sulfates Removal Via Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the specific conditions of this approach, a pH of 4 was determined optimal for sulfates adsorption. In the recent approach of Runtti et al (2017), adsorption of sulfates onto natural and/or modified zeolites has been shown to be effective under the lowest pH conditions (<6). These authors suggested that the enhancement of adsorbent state of protonation under acidic conditions favoured sulfates uptake.…”
Section: Sulfates Removal Via Adsorptionmentioning
confidence: 99%
“…Increasing sorption rates concomitant to growing SO 4 2- initial concentration was reported by several studies (Gobran et al, 1998; Gustaffson, 1995; Rose, 1998). While performing the adsorption of sulfates onto analcime and zeolites, Runtti et al (2017) underlined the importance of initial concentration during the interactive process. Different studies suggested that increasing SO 4 2- concentrations favours the driving forces of adsorption due to the settlement of a concentration gradient (Bhatnagar and Sillanpää, 2010; Runtti et al, 2017).…”
Section: Sulfates Removal Via Adsorptionmentioning
confidence: 99%
“…Inorganic adsorbents, such as limestone (Silva et al, 2012), modified alumino-silicate (analcime) (Runtti et al, 2017), and barium exchanged geopolymers (Runtti et al, 2016) can be used for sulfate adsorption with a sulfate adsorption capacity of 23.7, 13.0 and 119 mg • g −1 , respectively. Recently, biochar has attracted great attention as an alternative desirable adsorbent and catalyst support due to its porous structure, low cost and environmental compatibility (Jung & Ahn, 2016).…”
Section: Adsorption Of Sulfatementioning
confidence: 99%
“…Iron (Fe) and Sulfur (S) are metals and acids that are indicators of mining areas. The mining area can producing ironbased iron acids including pyrite (FeS2), pyrhotite (FeS), chalcopyrite (CuFeS) and arsenopyrite (FeAsS) (Commonwealt of Australia, 2016; Runtti et al, 2017). The high metal content of Fe hurts aquatic organisms such as low growth fish and can cause the death of aquatic organisms (Baby et al, 2010;Rajeshkumar and Li.…”
Section: Introductionmentioning
confidence: 99%
“…Physical reduction of Fe from water can be made with activated carbon (Syauqiah et al, 2011;Abdi et al, 2016), filtration (Giwa et al, 2017), zeolites (Runtti et al, 2017;Nur'Aini and Wilopo, 2017). Chemically, it can be done using chitosan (Burke et al, 2002;Lapo et al, 2019), and Chelating Agent (EDTA) (Aziz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%